Eating for the better: a social marketing review (2000–2012). Issue 7 (28th May 2013) - Carins, Julia E; Rundle-Thiele, Sharyn R
Abstract Objective The present study sought to identify both the ingredients for success and the potential impediments to social marketing effectiveness for healthy eating behaviour, focusing on studies conducted over the last 10 years. Design A comprehensive literature review was undertaken examining seventeen databases to identify studies reporting the use of social marketing to address healthy eating. Thirty-four empirical studies were analysed to examine the effectiveness of social marketing interventions to improve healthy eating behaviour using Andreasen's (2002) social marketing benchmark criteria. Statistical analysis was undertaken to quantitatively evaluate whether effectiveness varied between study categories (subsets). Setting Healthy eating empirical studies published from 2000 onwards. Subjects Empirical studies that self-identified as social marketing. Results Sixteen social marketing studies (subset 1) were identified in the review. These were systematic studies which sought to change behaviour through tailored solutions (e.g. use of marketing tools beyond communication was clearly evident) that delivered value to the target audience. For these sixteen studies, the mean number of criteria identified was five. Six studies met all six criteria. Positive change to healthy eating behaviour was found in fourteen of sixteen studies. The sixteen studies that met the definition of social marketing used significantly more of Andreasen's (2002) criteria and were more effective in achieving behavioural change than the eighteen studies in subset 2. Conclusions Social marketing is an involved process and it is important that studies identifying as social marketing adopt social marketing benchmark criteria. Social marketing when employed to its full extent offers the potential to change healthy eating.